2019
DOI: 10.5897/jlma2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of risks and returns on residential property sub-market in Lagos: Case study of 1004 Estate

Abstract: The study appraised the viability of investing in residential real estate submarket in Lagos State, using the apartments in 1004 Estate as case study with a view to providing a guide for investors and portfolio managers on investment decision-making in Lagos. Lagos, a mega city being a point of attraction to real estate investors makes it necessary to undertake real estate investment performance evaluation. To achieve this, the study ascertained the various risk status of each of the property submarkets and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The risk-return performance of RRE investment in the 1004 estate's property submarket of Lagos State was analysed by Okonu et al (2019). The study evaluated the total return and risk of investing in residential apartments within the estate and found that there was high risk associated with the returns in these apartments.…”
Section: Some Related Studies In Nigeriamentioning
confidence: 99%
“…The risk-return performance of RRE investment in the 1004 estate's property submarket of Lagos State was analysed by Okonu et al (2019). The study evaluated the total return and risk of investing in residential apartments within the estate and found that there was high risk associated with the returns in these apartments.…”
Section: Some Related Studies In Nigeriamentioning
confidence: 99%
“…The performance of residential property investment in Lagos State was assessed by Okonu et al (2019), using 1004 residential estate as a case study. The data, which were retrieved from the managing company for the period from 2010 to 2017, was analysed and the return-to-risk ratio determined.…”
Section: Studies That Compared Performance Of Direct Real Estate Investment Assets In Nigeriamentioning
confidence: 99%
“…If the cost is higher than the market value of the project, it brings losses. (Okonu, Umeh, Akinwande, and Muraina, 2019). According to Bahamid, Doh and Al-Sharai (2019), "reduction of risk is a major task in real estate delivery process, while uncertainty is the main condition within which real estate project is implemented."…”
Section: Introductionmentioning
confidence: 99%